The feminine condition: women and madness in Katherine Mansfield`s "Prelude" - Dodson-Castillón, Cristina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article discusses the representation of women and mental illness in Katherine Mansfield`s short story, "Prelude". The theme of madness and psychology in feminist literary criticism has been an active field of contemporary research. Critics such as Phyllis Chesler, Elaine Showalter, and Jane Ussher view some forms of madness as traditionally gendered, feminine conditions in which women become mad due to their oppressive realities.
Keywords: women and madness; gender studies; modernism; Mansfield, Katherine (pseud.); Mansfield Murry, Kathleen (1888-1923) - studies; madness as rebellion